Polymer-graphene nanocomposites - Mittal, Vikas (RSC nanoscience & nanotechnology ;, 2012)
"Graphene is an emerging material for generating polymer nanocomposites. Its heat conducting properties are greater than any other material, yet so dense not even helium can pass through its honeycomb lattice. The inclusion of small amounts of graphene to polymer matrices has the possibility of significantly improving their electrical, barrier and mechanical properties. Since the Nobel prize for Physics was awarded in 2010 for the isolation of graphene there has been an explosion in graphene research and the discovery of new applications. This book discusses the current state-of-the-art in graphene nanocomposites with expertise drawn from across the globe. Insights into the functionalisation of graphene are presented, in the context of various polymer systems, along with appropriate methodologies to be adopted. Grasping this view from several active researchers in the field gives the editor the opportunity to look where future trends are heading. This is an important handbook for anyone wishing to get a comprehensive view of the field and bring established methodologies into their laboratory and will benefit post-graduate students and established researchers alike."--